Cost‐effectiveness of treating chronic hepatitis C virus with direct‐acting antivirals in people who inject drugs in Australia. Issue 4 (April 2016) - Scott, Nick; Iser, David M; Thompson, Alexander J; Doyle, Joseph S; Hellard, Margaret E
Abstract: Background and Aim: Reducing the burden of hepatitis C virus (HCV) related liver disease will require treating people who inject drugs (PWID), the group at most risk of infection and transmission. We determine the cost‐effectiveness of treating PWID with interferon‐free direct‐acting antiviral therapy in Australia. Methods: Using a deterministic model of HCV treatment and liver disease progression, including a fixed rate of re‐infection, the expected healthcare costs and quality‐adjusted life years (QALYs) of a cohort of newly HCV‐infected PWID were calculated for: no treatment; treatment after initial infection ("early‐treatment"); and treatment prior to developing compensated cirrhosis ("late‐treatment"). Incremental cost‐effectiveness ratios (ICERs) were used to compare scenarios. Results: Late‐treatment was cost‐effective compared to no treatment, with a discounted average gain of 2.98 (95%confidence interval 2.88–5.22) QALYs per person for an additional cost of $15 132 ($11 246–18 922), giving an ICER of $5078 ($2847–5295) per QALY gained. Compared to late‐treatment, early‐treatment gained a further discounted average of 2.27 (0.58–4.80) QALYs per person for $38 794 ($34 789–41 367), giving an ICER of $17 090 ($2847–63 282), which was cost‐effective in approximately 90% of Monte‐Carlo uncertainty simulations. For every 100 newly HCV‐infected PWID, there were an estimated 40 (39–56) eventual liver‐related deaths without treatment, compared to 7 (6–11) and 8 (7–13) with early‐treatment and late‐treatment available respectively. Conclusions: Treating HCV‐infected PWID with new therapies is cost‐effective and could prevent a significant number of liver‐related deaths. Although late‐treatment was the most cost‐effective option, the cost per QALY gained for early‐treatment compared to late‐treatment is likely to be below unofficial Australian willingness to pay thresholds.